Bribery and the Role of Public Service Motivation and Social Value Orientation: A Multi-Site Experimental Study in Belgium, Germany and the Netherlands - De Waele, Lode; Weißmüller, Kristina S.; van Witteloostuijn, Arjen (Frontiers in Psychology, 2021)
Bribery is a complex phenomenon rooted in both individual motives and the greater institutional context. Experimental research into causal mechanisms that drive bribing behavior is still scarce. To date, there is no empirical evidence on how the society-regarding attitude of Public Service Motivation (PSM) and the other-oriented trait of Social Value Orientation (SVO) can help explain why some people are more susceptible to engage in the act of bribing than others. Based on a multi-site triple-replication, vignette-based research design, quasi-experimental evidence from Belgium, Germany, and the Netherlands shows that both measures interact and that – paradoxically – people with higher SVO are more likely to be willing to engage in bribery.